A design of radial line slot array antennas using the specification of panel antennas - Teddy Purnamirza; Muhammad Ralibi; Imran M. Bin Ibrahim; Rika Susanti; Halim Mudia; Depriwana Rahmi; Sutoyo Sutoyo; Mulyono Mulyono (Universitas Ahmad Dahlan, 2019)
RLSA antennas were suggested by several researches as Wi-Fi antennas in addition to panel antennas. Therefore, this paper researched the possibility of this suggestion. We used the size of an available in market 16 dBi panel antenna (225 mm2) as the size for our developed RLSA antenna. Based on this size, we developed 60 RLSA models using extreme beamsquint technique and simulated them. We then chose a best model with a best performance. The best model was then fabricated and measured. The simulation and measurement results show that the developed RLSA antenna has better performance compared to the 16 dBi panel antenna in term of gain (0.25 dB higher) and bandwidth (570 MHz wider). The RLSA antenna also tested as antenna for a Wi-Fi device and it showed good performance.